Silver nanowire-polyimide flexible transparent substrate electrode and preparation method thereof
By regulating the degree of AgNWs embedded in CPI in the AgNWs/CPI flexible transparent substrate electrode, and using the solvent post-annealing treatment process, the problem of uncontrollable AgNWs embedded in the AgNWs is solved, and the AgNWs/CPI flexible transparent substrate electrode with high conductivity, high light transmittance and low surface roughness is achieved, meeting the application needs of flexible electronic devices.
Patent Information
- Application Number
- CN202211062640.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-01
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2042-09-01
AI Technical Summary
The degree to which the existing silver nanowire-polyimide flexible transparent substrate electrodes are uncontrollable in AgNWs, resulting in reduced conductivity and cannot meet the needs of practical applications.
By coating the AgNWs diluted solution on the substrate, then applying the soluble CPI solution and curing gradient temperature, followed by defiling and post-solvent annealing treatment, the degree of AgNWs embedded in CPI was adjusted, and an AgNWs/CPI flexible transparent substrate electrode with controllable embeddedness was prepared.
The high conductivity, high light transmittance, low surface roughness and high adhesion of AgNWs/CPI flexible transparent substrate electrodes are achieved, meeting the application needs of flexible electronic devices.
Smart Images

Figure CN115274216B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a silver nanowire-polyimide flexible transparent substrate electrode and a preparation method thereof, and in particular to a silver nanowire-polyimide flexible transparent substrate electrode with a controllable degree of embedding of silver nanowires AgNWs into a polymer and a low resistance and a preparation method thereof. Background Art
[0002] Glass / indium tin oxide (hereinafter referred to as ITO) substrate electrodes have always dominated the traditional electronic device market due to their many advantages such as good light transmittance, excellent conductivity, and mature manufacturing technology. They are widely used in electronic devices such as light-emitting diodes, solar cells, flat-panel displays, and touch screens.
[0003] However, glass / ITO electrodes have the following defects: on the one hand, glass as a substrate is heavy, hard, and fragile; on the other hand, ITO as a conductive layer is a brittle material with poor flexibility, and its conductivity decreases significantly with the increase of bending degree. In addition, the raw material indium resources are scarce and the cost is increasing year by year. With the advent of the curved and flexible era, glass / ITO electrodes can no longer meet the development needs of lightweight and flexible electronic devices. Therefore, the development of high-performance flexible transparent substrate electrodes is a bottleneck problem that needs to be solved urgently in the field of flexible electronic devices.
[0004] Among flexible substrate materials, colorless and transparent polyimide (hereinafter referred to as CPI) has excellent high temperature resistance, excellent chemical stability and biocompatibility, good bending resistance, and high light transmittance, which is suitable for providing flexible substrates for devices. Among flexible conductive layer materials, silver nanowires (hereinafter referred to as AgNWs) not only have the characteristics of high light transmittance, high conductivity and good flexibility, but also have simple synthesis methods and are easy to prepare on a large scale. They are considered to be the most promising flexible conductive layer material to replace ITO. Therefore, the composite of AgNWs and CPI to produce flexible transparent substrate electrodes has important research significance and great application potential.
[0005] However, the existing process of directly coating / sprinkling the AgNWs solution on the substrate by spin coating, scraping or spraying to dry the film still has problems such as high surface roughness and poor adhesion between AgNWs and the substrate, which limits the application and industrialization of silver nanowire-polyimide (hereinafter referred to as AgNWs / CPI) flexible transparent substrate electrodes. In order to reduce the surface roughness of the electrode and improve the adhesion between AgNWs and the substrate, a substrate transfer method can be used, such as: a method for preparing a silver nanowire-peelable resin composite transparent conductive film disclosed in patent document CN107316708B. First, the AgNWs are embedded in a liquid polymer, and then the polymer is cured to embed the AgNWs in the polymer, and finally the AgNWs / polymer is peeled off from the originally deposited substrate. This can not only effectively reduce the surface roughness of the AgNWs electrode, but also solve the problem of poor adhesion between the AgNWs and the substrate. However, the existing substrate transfer method for embedding AgNWs into polymer substrates still has problems such as the uncontrollable degree of embedding of AgNWs into polymers, excessive embedding resulting in a large number of AgNWs not participating in conduction, thereby reducing the conductivity of the electrode, and therefore cannot meet the needs of practical applications.
[0006] Therefore, it is urgent to develop a method for preparing AgNWs / CPI flexible transparent substrate electrodes in which the degree of AgNWs embedded in polymer is uncontrollable. Summary of the invention
[0007] The technical problem to be solved by the present invention is to provide a low-resistance AgNWs / CPI flexible transparent substrate electrode with a controllable degree of embedding of silver nanowires AgNWs into a polymer and a preparation method thereof.
[0008] In order to solve the above technical problems, the present invention first provides a method for preparing an AgNWs / CPI flexible transparent substrate electrode, which specifically comprises the following steps:
[0009] (1) coating a diluted AgNWs solution on a substrate to obtain an AgNWs conductive layer;
[0010] (2) dissolving soluble CPI powder into a first solvent to obtain a CPI solution, and coating the solution on the AgNWs conductive layer, and gradually increasing the temperature after the solution is evenly diffused to solidify the CPI into a film;
[0011] (3) After the curing is completed, the film is stripped to obtain a composite film in which AgNWs are embedded in CPI;
[0012] (4) uniformly coating a second solvent capable of dissolving CPI on the AgNWs conductive surface of the composite film obtained in step (3), and performing a solvent post-annealing treatment to obtain the AgNWs / CPI flexible transparent substrate electrode.
[0013] Furthermore, in step (4), the amount of the second solvent applied is 10 to 30 μL / cm 2 More specifically, in a possible embodiment, illustratively, the amount of the second solvent applied may be, but is not limited to, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30 μL / cm 2 .
[0014] Further, the solvent post-annealing treatment process in step (4) is: temperature 60°C to 200°C, time 30min to 6h. Further, the solvent post-annealing treatment process is: temperature 100°C to 150°C, time 1h to 3h.
[0015] Furthermore, the substrate in step (1) is a rigid substrate such as silicon wafer, glass, etc. or a flexible substrate such as PET, PEN, etc. Preferably, the substrate is cleaned before coating the diluted AgNWs solution.
[0016] Furthermore, the coating method in step (1) is spin coating, drop coating, blade coating, spray coating, roll coating, dip coating, or vacuum filtration.
[0017] Furthermore, the AgNWs dilution solution in step (1) is obtained by dispersing AgNWs in at least one solvent selected from the group consisting of deionized water, ethanol, isopropanol, ethylene glycol, and polyethylene glycol.
[0018] Further, the concentration of the AgNWs diluted solution in step (1) is 0.5 mg / mL to 10 mg / mL. Preferably, it is 2 mg / mL to 6 mg / mL. Specifically, in possible embodiments, illustratively, the concentration of the AgNWs diluted solution can be, but is not limited to, 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 8, 8.5, 9, 10 mg / mL.
[0019] Furthermore, in step (2), the first solvent may be, but is not limited to, at least one of DMAC (dimethylacetamide), DMF (N,N-dimethylformamide), DMSO (dimethyl sulfoxide), and THF (tetrahydrofuran).
[0020] Preferably, the mass percentage of the CPI solution in step (2) is 10-20wt%. Specifically, in possible embodiments, illustratively, the mass percentage of the CPI solution can be, but is not limited to, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%.
[0021] Furthermore, the coating method in step (2) is spin coating or blade coating.
[0022] Furthermore, the gradient temperature rising condition in step (2) is to maintain the temperature at 60°C, 120°C and 200°C for 30 minutes in sequence.
[0023] Furthermore, the demoulding process of step (3) is generally performed by immersing in deionized water. The demoulding process can be completed by immersing in deionized water at room temperature for 10 to 20 minutes.
[0024] Furthermore, the second solvent capable of dissolving CPI in step (4) may be, but is not limited to, at least one of DMAc, DMF, DMSO, and THF.
[0025] Furthermore, the coating method in step (4) is drop coating, spin coating, blade coating or dip coating.
[0026] The present invention also provides an AgNWs / CPI flexible transparent substrate electrode prepared by the above preparation method, specifically a composite film formed by using soluble CPI as a substrate and AgNWs semi-embedded in CPI.
[0027] Preferably, the AgNWs / CPI flexible transparent substrate electrode has a square resistance lower than 20Ω / sq, a light transmittance greater than 90% at 550nm, and a surface roughness lower than 20nm.
[0028] Beneficial effects of the present invention:
[0029] The flexible transparent substrate electrode of the present invention is composed of soluble CPI and AgNWs. The method of the present invention first embeds AgNWs into soluble CPI, and etches its surface through solvent post-annealing treatment technology, thereby obtaining an AgNWs / CPI flexible transparent substrate electrode with controllable embedding degree and low resistance.
[0030] The solvent post-annealing treatment process in the method of the present invention can effectively solve the problem that the existing substrate transfer method has uncontrollable embedding degree of AgNWs. The embedding degree of AgNWs in CPI can be controlled by adjusting the amount of coating solvent, processing temperature and processing time, thereby obtaining an AgNWs / CPI flexible transparent substrate electrode with high conductivity, high transmittance, low surface roughness and high adhesion.
[0031] The AgNWs / CPI flexible transparent substrate electrode prepared by the method of the present invention is tested for sheet resistance, transmittance, surface roughness and adhesion of the film. The results show that the sheet resistance of the flexible transparent substrate electrode prepared by the method is lower than 20Ω / sq, the transmittance at 550nm is greater than 90%, the surface roughness is lower than 20nm, and the sheet resistance remains almost unchanged after 500 bending times.
[0032] The preparation method provided by the invention is simple to operate, highly repeatable and has practical application value. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0034] Figure 1 This is a SEM image of the microstructure of the sample prepared in Example 1 of the present invention;
[0035] Figure 2 This is a SEM image of the microstructure of the sample prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0036] The invention is further described below in conjunction with the embodiments and drawings, but they are not intended to limit the scope of the invention.
[0037] Example 1
[0038] This embodiment provides a method for preparing an AgNWs / CPI flexible transparent substrate electrode, which specifically includes the following steps:
[0039] (1) A 1.5 cm × 1.5 cm glass substrate was cleaned and spin-coated with an ethanol diluted solution of AgNWs at a speed of 500 rpm / min. The concentration of the solution was 2 mg / mL. After the solution was evenly diffused, an AgNWs conductive layer was obtained.
[0040] (2) The soluble CPI powder was dissolved into a solution with a mass fraction of 15 wt% in the solvent of DMAc, and was spin-coated on the AgNWs conductive layer at a speed of 500 rpm / min. After the solution was evenly diffused, the sample was placed on a heating table for gradient heating. The heating conditions were maintained at 60°C, 120°C and 200°C for 30 min in sequence to allow the CPI to solidify into a film.
[0041] (3) immersing the cured sample in deionized water for film stripping to obtain a composite film in which AgNWs are embedded in CPI;
[0042] (4) Use a pipette to take 45 μL of DMAc solution and evenly drop it on the AgNWs conductive surface of the obtained composite film, and place it on a heating table for solvent post-annealing treatment at a temperature of 100 °C for 1 h to obtain an AgNWs / CPI flexible transparent substrate electrode, which is recorded as sample S1.
[0043] Example 2
[0044] The difference between Example 2 and Example 1 is that step (4) is:
[0045] Use a pipette to take 67.5 μL of DMAc solution and evenly drop it on the AgNWs conductive surface of the obtained composite film, and place it on a heating table for solvent post-annealing treatment at a temperature of 100°C for 1 h to obtain an AgNWs / CPI flexible transparent substrate electrode, recorded as sample S2.
[0046] Example 3
[0047] The difference between Example 3 and Example 1 is that step (4) is:
[0048] (4) Use a pipette to take 22.5 μL of DMAc solution and evenly drop it on the AgNWs conductive surface of the obtained composite film, and place it on a heating table for solvent post-annealing treatment at a temperature of 100 °C for 1 h to obtain an AgNWs / CPI flexible transparent substrate electrode, which is recorded as sample S3.
[0049] Example 4
[0050] The difference between Example 3 and Example 1 is that:
[0051] The ethanol diluted solution of AgNWs in step (1) has a concentration of 10 mg / mL;
[0052] In step (4), the coating amount of DMAc solution is 22.5 μL, the annealing temperature is 60° C., and the time is 6 h, to obtain a AgNWs / CPI flexible transparent substrate electrode, which is recorded as sample S4.
[0053] Example 5
[0054] The difference from Example 1 is:
[0055] The AgNWs dilution solution in step (1) is a deionized water dispersion dilution solution with a solution concentration of 10 mg / mL;
[0056] The solvent in step (2) is DMSO, and the mass percentage of the CPI solution is 10wt%;
[0057] The solvent for dissolving CPI in step (4) is THF, the coating amount of THF is 45 μL, the annealing temperature is 150° C., and the time is 3 h, to obtain an AgNWs / CPI flexible transparent substrate electrode, which is recorded as sample S5.
[0058] Example 6
[0059] The difference from Example 1 is:
[0060] The AgNWs dilution solution in step (1) is a deionized water dispersion dilution solution with a solution concentration of 6 mg / mL;
[0061] The solvent in step (2) is THF, and the mass percentage of the CPI solution is 20wt%;
[0062] The solvent for dissolving CPI in step (4) is DMF, the coating amount of DMF is 45 μL, the annealing temperature is 200° C., and the time is 30 min, to obtain an AgNWs / CPI flexible transparent substrate electrode, which is recorded as sample S6.
[0063] Comparative Example 1
[0064] Comparative Example 1 provides a method for preparing an AgNWs / CPI flexible transparent substrate electrode, which specifically includes the following steps:
[0065] (1) A 1.5 cm × 1.5 cm glass substrate was cleaned and spin-coated with an ethanol diluted solution of AgNWs at a speed of 500 rpm / min. The concentration of the solution was 2 mg / mL. After the solution was evenly diffused, an AgNWs conductive layer was obtained.
[0066] (2) The soluble CPI powder was dissolved into a solution with a mass fraction of 15 wt% in the solvent of DMAc, and was spin-coated on the AgNWs conductive layer at a speed of 500 rpm / min. After the solution was evenly diffused, the sample was placed on a heating table for gradient heating. The heating conditions were maintained at 60°C, 120°C and 200°C for 30 min in sequence to allow the CPI to solidify into a film.
[0067] (3) The cured sample was immersed in deionized water for demolding to obtain a composite film of AgNWs embedded in CPI, namely, AgNWs / CPI flexible transparent substrate electrode, which was recorded as sample D1.
[0068] In order to verify the performance and effect of the samples prepared by the preparation method provided in the above embodiment, the flexible transparent substrate electrode samples prepared in the above embodiment and comparative example were subjected to the following tests:
[0069] 1. Scanning electron microscope (SEM) analysis was performed on the flexible transparent substrate electrode samples prepared in Examples 1-6 and Comparative Example 1. The results are as follows: Figure 1 , Figure 2 As shown. Figure 1 As shown, after the solvent post-annealing treatment under the experimental conditions, the silver nanowires in Example 1 were in a semi-embedded state, and the surface of the polyimide substrate was flat. The samples prepared in other examples also had similar microscopic morphologies. Figure 2As shown, in the sample of comparative example 1 treated with solvent-free post-annealing, the polyimide over-coated the silver nanowires, the surface was obviously concave-convex, and the electrode square resistance was large.
[0070] 2. The square resistance, transmittance, surface roughness and adhesion of the flexible transparent substrate electrodes prepared in the above embodiments and comparative examples were tested. The specific testing methods are as follows: a four-probe resistance meter was used to test its square resistance, a UV-visible spectrophotometer was used to test its transmittance at 550nm, and the surface roughness was measured by a step profiler.
[0071] The test results are shown in Table 1:
[0072] sample Square resistance (Ω / sq) Transmittance (550nm) Surface roughness(nm) Adhesion S1 12.7 92% 8 The square resistance remains almost unchanged after 500 bendings S2 8.2 92% 13 The square resistance remains almost unchanged after 500 bendings S3 17.5 92% 5 The square resistance remains almost unchanged after 500 bendings S4 11.3 89% 9 The square resistance remains almost unchanged after 500 bendings S5 4.1 89% 19 The square resistance remains almost unchanged after 500 bendings S6 6.9 90% 17 The square resistance remains almost unchanged after 500 bendings D1 104.1 92% 3 The square resistance remains almost unchanged after 500 bendings
[0073] In summary, in the preparation method of the embodiment of the method of the present invention, the use of solvent post-annealing treatment process can effectively solve the problem that the existing substrate transfer method cannot control the degree of AgNWs embedding, and the degree of AgNWs embedding in CPI can be controlled by adjusting the amount of coating solvent, processing temperature and processing time, thereby obtaining an AgNWs / CPI flexible transparent substrate electrode with high conductivity, high transmittance, low surface roughness, and high adhesion. In addition, the method of the present invention is simple to operate and highly repeatable.
[0074] The above descriptions are only some preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a silver nanowire-polyimide flexible transparent substrate electrode, characterized in that: The specific steps include: (1) coating a diluted AgNWs solution on a substrate to obtain an AgNWs conductive layer; (2) dissolving soluble CPI powder into a first solvent to obtain a CPI solution, and coating the solution on the AgNWs conductive layer, and gradually increasing the temperature after the solution is evenly diffused to solidify the CPI into a film; (3) After the curing is completed, a demolding treatment is performed to obtain a composite film in which AgNWs are embedded in CPI; (4) uniformly coating a second solvent capable of dissolving CPI on the AgNWs conductive surface of the composite film obtained in step (3), and performing a solvent post-annealing treatment to obtain the AgNWs / CPI flexible transparent substrate electrode; The amount of the second solvent applied is 10 to 30 μL / cm 2 The solvent post-annealing treatment process is: temperature 60℃~200℃, time 30min~6h.
2. The method for preparing the silver nanowire-polyimide flexible transparent substrate electrode according to claim 1, characterized in that: The substrate in step (1) is a rigid substrate or a flexible substrate. The rigid substrate includes silicon wafer and glass; the flexible substrate includes PET and PEN.
3. The method for preparing the silver nanowire-polyimide flexible transparent substrate electrode according to claim 1 or 2, characterized in that: The AgNWs dilution solution in step (1) is obtained by dispersing AgNWs in at least one solvent selected from deionized water, ethanol, isopropanol, ethylene glycol, and polyethylene glycol; the concentration of the AgNWs dilution solution is 0.5 mg / mL to 10 mg / mL.
4. The method for preparing the silver nanowire-polyimide flexible transparent substrate electrode according to claim 1 or 2, characterized in that: The coating method in step (1) is spin coating, drop coating, scraper coating, spray coating, roll coating, dip coating or vacuum filtration; The coating method in step (2) is spin coating or blade coating; The coating method in step (4) is drop coating, spin coating, blade coating or dip coating.
5. The method for preparing the silver nanowire-polyimide flexible transparent substrate electrode according to claim 1 or 2, characterized in that: The first solvent in step (2) is at least one of DMAc, DMF, DMSO and THF.
6. The method for preparing the silver nanowire-polyimide flexible transparent substrate electrode according to claim 1 or 2, characterized in that: The gradient temperature rising condition in step (2) is to maintain the temperature at 60°C, 120°C and 200°C for 30 minutes in sequence.
7. The method for preparing the silver nanowire-polyimide flexible transparent substrate electrode according to claim 1 or 2, characterized in that: In step (4), the second solvent capable of dissolving CPI is at least one of DMAc, DMF, DMSO and THF.
8. The method for preparing the silver nanowire-polyimide flexible transparent substrate electrode according to claim 1 or 2, characterized in that: The mass percentage of the CPI solution in step (2) is 10-20wt%.
9. A silver nanowire-polyimide flexible transparent substrate electrode prepared by the preparation method according to any one of claims 1 to 8, characterized in that: Specifically, soluble CPI is used as a substrate, and AgNWs are semi-embedded in CPI to form a composite film.
Citation Information
Patent Citations
Preparation method of silver nanowire-exfoliable resin composite transparent conductive film
CN107316708B
Preparation method for flexible transparent conductive thin film with high thermal stability and product thereof
CN105405492A
Flexible organic thin film transistor and fabrication method thereof
CN109638158A